2022
DOI: 10.2196/33394
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Exposure to Mass Media on Growth Stunting Among Children Under Five: Mediation Analysis Through the Water, Sanitation, and Hygiene Program

Abstract: Background The issue of malnutrition in the Democratic Republic of Congo is severe. Meanwhile, the Water, Sanitation, and Hygiene program has been demonstrated to be effective in reducing the rates of growth stunting among children. Objective We aimed to explore the association between maternal exposure to mass media and stunting in children through water, sanitation, and hygiene behaviors. Methods Mediation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Some results of studies stated that the risk of stunting in children is reduced when there is improved household water, sanitation, and hygiene practices, which may be increased by mothers' exposure to television and the internet. As far as we are aware, this is the first study to use route analysis to examine the relationship between media exposure and stunting (Huo et al, 2022). In order to develop and implement effective interventions, it will be necessary to comprehend the contributions of the various stunting risk factors in order to meet the WHO milestones for reducing stunting.…”
Section: Resultsmentioning
confidence: 99%
“…Some results of studies stated that the risk of stunting in children is reduced when there is improved household water, sanitation, and hygiene practices, which may be increased by mothers' exposure to television and the internet. As far as we are aware, this is the first study to use route analysis to examine the relationship between media exposure and stunting (Huo et al, 2022). In order to develop and implement effective interventions, it will be necessary to comprehend the contributions of the various stunting risk factors in order to meet the WHO milestones for reducing stunting.…”
Section: Resultsmentioning
confidence: 99%
“…The material revolves around: How to prevent stunting with hygiene and sanitation (WASH: Water, Sanitation, Hygiene). Things that must be considered: (1) Washing hand using water and soap; Using Healthy Latrines (2M), (2) Securing and Managing Household Garbage and Waste Disposal; Management of drinking water and household food; Clean water supply (3P) and WASH [25], [31]. Provided material begin by conducting pretest to students.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that access to media has a direct influence on health behaviours [ 53 ], including nutrition behaviours [ 54 ] in sub-Saharan Africa [ 55 ] and other South Asian countries [ 56 ], including Bangladesh [ 57 ]. Therefore, the study findings are consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%